Contemporary Epidemiology of Catheter-Associated Urinary Tract Infections (CAUTIs) in a Tertiary Care Center: Is Foley Re-Insertion a Novel Risk Factor?. (4th October 2017) - Nowbakht, Cima; Boston, Kelley M; Harrison, Nicole; Patel, Bela; Katz, Jeffrey; Ostrosky-Zeichner, Luis
Abstract: Background: CAUTIs are one of the most common causes of hospital-acquired infections. We report on a retrospective analysis performed on prospectively collected CAUTI surveillance data from 2014 to 2016 at a large tertiary care academic hospital Methods: A total of 181 CAUTIs by NHSN definition were reviewed to describe contemporary demographics, risk factors, microbiology, and outcomes. Results: The 181 CAUTIs involved 178 patients. 61% were female. Events mostly occurred in an ICU setting (65%), specifically our neurosurgical unit (23%), followed by floors (24%) and intermediate units (11%). Most episodes occurred within a week after the initial catheter insertion (60%). 40% of CAUTIs occurred within an average of 5.5 days (SD ± 5.12) after a Foley re-insertion. Of the 221 cultured micro-organisms, Gram-negatives accounted for 74% (predominately K. pneumoniae and E. coli), followed by Gram-positives and yeast at 18% and 8%, respectively. 8% of organisms showed multi-drug resistance, 8% of patients developed C. difficile co-infections, 23% had concomitant bacteremia, and the length of stay averaged 28 days (SD ± 26.74). 55% of patients were discharged to another facility. 12% of patients expired and 4% were discharged to hospice Conclusion: We describe the contemporary demographics, microbiology and outcomes of CAUTIs in a large tertiary care center. We also found that 40% of our CAUTIS are associated with a Foley removal and re-insertion event. Reasons requiring catheter exchanges and reinsertions include leakage, bleeding, obstruction, failed voiding trial, and general malfunction. Although this observation needs to be confirmed case control studies and larger observational trials, this new insight may provide an opportunity to intervene and focus infection prevention interventions in this novel high-risk population. Disclosures: All authors: No reported disclosures.